Understanding Psychological Safety in Agile Software Development Teams - Monte, Lidivânio; Santana, Beatriz; Carneiro, Glauco de Figueiredo; Mendonça, Manoel; Freire, Sávio; Santos, José Amancio Macedo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.9974, 2025)
Context: Psychological safety (PS) refers to individuals’ perceptions of the interpersonal risks of speaking up or making mistakes in team environments. In agile software development, PS is especially relevant due to its emphasis on collaboration, iteration, and continuous feedback. Despite growing interest in PS, there is still a limited understanding of how specific situations in agile contexts trigger psychological insecurity. Aims: This study aims to identify situations that challenge PS in agile teams, explore the causes behind these situations, and analyze their effects on team members and processes. Method: We conducted a qualitative content analysis of 54 discussions from Stack Exchange forums, focusing on real-life agile development experiences. Results: We identified five categories of challenging situations (e.g., misalignment of agile roles and responsibilities), seven categories of causes (e.g., process conflicts and bureaucracy), and five categories of consequences (e.g., team management and dynamic issues). Besides, we found frequent co-occurrence patterns between causes and consequences, revealing how PS disruptions propagate in agile teams. Conclusion: By categorizing real-world PS challenges, this study offers actionable directions for agile practitioners to recognize, anticipate, and mitigate psychologically unsafe conditions. Our taxonomy contributes to a more practical and nuanced understanding of PS in agile environments, supporting both empirical research and organizational interventions.